Operation of the small glaciated catchment geosystem (Arie, Spitsbergen) - Nawrot, Adam Piotr (My University, 2011)
To recognize operation of the small glaciated catchment geosystem, scientific investigation had taken place between April 2007 and August 2009. The main goal was to determine water balance and matter flux of the small cold body glacier’s basin. The investigation was made in Arie glacier basin (Hornsund) and it was the first integrated monitoring study of Arie Valley, which included meteorology, glaciology, hydrology and hydrochemistry. Supply of matter sources to the catchment geosystem, fluvial transport conditions, seasonal fluctuation of the operation of glaciated basin geosystem and Arie glacier mass balance for 2006/2007, 207/2008, 2008/2009 seasons was determined. To recognize temporal evolution of the Arie valley bottom and role of Arie ice-core moraine in mater circulation, dendrochronological and isotopic (radon 222Rn) methods were used. As a result, development of the qualitative and quantitative model of the water balance and matter flux in the small Arctic glaciated basin was made. In 2008 it was noticed, that the highest mechanical denudation was in June and September. 15% of total solute matter was supplied from marine aerosols and 1% from atmosphere. Participation in annual water balance as follow: snow and rain (74%), Arie glacier (15%) and ice-moraine (1%). In water balance calculation permafrost active layer and atmospheric deposits were not included. Because water balance estimation for Arctic basins is difficult and rarely presented in scientific papers, this kind of study presented here is strongly required for expanding knowledge about operation of the small glaciated geosystems.

Od kwietnia 2007 do sierpnia 2009 prowadzono badania nad rozpoznaniem funkcjonowania geosystemu małej zlewni zlodowaconej SW Spitsbergenu. Celem pracy było określenie bilansu wodnego oraz obiegu materii w basenie małego lodowca zimnego. Do badań wytypowano zlewnię lodowca Arie (Hornsund). Prowadzone badania były pierwszymi badaniami zlewni Arie (2.04 km2) o charakterze zorganizowanego monitoringu i obejmował: meteorologię, glacjologię, hydrologię oraz hydrochemię. Określono źródła dostawy materii do geosystemu zlewni, rozpoznano uwarunkowania transportu fluwialnego rzeki Arie, określono zmienność sezonową funkcjonowania geosystemu zlewni zlodowaconej, obliczono bilans lodowca Arie dla sezonów 2006/2007, 2007/2008, 2008/2009. Zastosowanie metody dendrochronologicznej oraz izotopowej (radon 222Rn), pozwoliło określić tempo rozwoju dna doliny i funkcję moreny Arie w obiegu materii. Opracowano jakościowy i ilościowy model bilansu wodnego i obiegu materii małej arktycznej zlewni zlodowaconej. W roku 2008 wykazano największą aktywność denudacji mechanicznej w czerwcu oraz we wrześniu; udział jonów pochodzenia morskiego (15%) oraz atmosferycznego (1%); udział śniegu i deszczu w rocznym bilansie wodnym zlewni Arie (74%), lodu lodowca Arie (15%) oraz moreny z jądrem lodowym (1%). Nie uwzględniono w bilansie udziału warstwy czynnej zmarzliny i osadów atmosferycznych. Opracowanie bilansu wodnego zlewni Arktycznych jest trudne i rzadko w literaturze prezentowane. Praca ta rozszerza dotychczasową wiedzę w zakresie rozpoznania funkcjonowania niewielkich geosystemów polarnych.
Funkcjonowanie geosystemu małej zlewni zlodowaconej (Arie, Spitsbergen)
Wydział Nauk Geograficznych i Geologicznych: Instytut Geoekologii i Geoinformacji
Keywords: Arctic; Arktyka; Spitsbergen; glacier; lodowiec; water balance; bilans wodny; matter flux; przepływ materii